Development of Psychoeducational Media for Cancer Patients and Their Families in the Community - Lukman; Ningsih, Nurna; Sanjaya, Erie; Rahmadania, Cahya; Julia (International Journal Scientific and Professional, 2025)
This research aims to develop effective psychoeducational media for cancer patients and their families in the community. Psychoeducation not only provides medical information, but also supports the emotional and psychological aspects faced by patients and their families. This study uses a Research and Development (R&D) approach with data collection through in-depth surveys and interviews with cancer patients, families, and health workers. The psychoeducational media developed includes brochures, educational videos, and mobile applications that are easily accessible and understood. The results of the trials showed that this medium was effective in improving cancer patients' understanding of their disease, reducing anxiety, and improving emotional support. This research is expected to be a model in the development of community-based health education media to improve the quality of life of cancer patients and their families.